What's in it for us? Staff perspectives on the impact of implementing positive behavior support - Fathi Abou Zaid (Social Sciences and Humanities Open)
A social environment conducive to learning is important for students to achieve educational goals. Well-functioning leadership in the classroom creates conditions for teaching, learning, and development. The aim of this study was to investigate how staff perceive and receive a positive behavior support (PBS) program two years after its implementation and how it affects the social environment conducive to learning. The researcher conducted and analyzed three group interviews, one pair interview and one individual interview with teachers and principals (N = 14) through reflexive thematic analysis. The results showed that the staff perceived no visible result concerning the students' behavior after the implementation of PBS. However, the staff experienced positive results in leadership skills, teamwork, their ability to create a culture that favors a social environment conducive to learning, and how to handle students. The findings also showed that the staff had a positive view of PBS; the program gave them concrete strategies that made it easier to create expectations. Some staff were unable to participate, and additional time and resources were required. The study's results help us understand the impact of PBS in Sweden, which has not been researched thoroughly to date.